2018
DOI: 10.5194/amt-2018-240
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Validation of the TOLNet Lidars: The Southern California Ozone Observation Project (SCOOP)

Abstract: Abstract. The North-America-based Tropospheric Ozone Lidar Network (TOLNet) was recently established to provide high spatio-temporal vertical profiles of ozone, to better understand physical processes driving tropospheric ozone variability, and to validate the tropospheric ozone measurements of upcoming space-borne missions such as Tropospheric Emissions:Monitoring Pollution (TEMPO). The network currently comprises six tropospheric ozone lidars, four of which are mobile 25 instruments deploying to the field a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

6
1

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…As part of these efforts, TOLNet lidar teams have collectively developed rigorous instrument procedures and processing algorithms to ensure consistency in O 3 data products and associated uncertainties between instruments (Leblanc et al, 2016a, b). Crosscomparison studies conducted between TOLNet lidar systems (Leblanc et al, 2018;Wang et al, 2017;Sullivan et al, 2015) showed that O 3 profile concentrations typically agree within ±5%, consistent with system specific propagated errors.…”
Section: The Langley Mobile Ozone Lidar (Lmol)mentioning
confidence: 55%
“…As part of these efforts, TOLNet lidar teams have collectively developed rigorous instrument procedures and processing algorithms to ensure consistency in O 3 data products and associated uncertainties between instruments (Leblanc et al, 2016a, b). Crosscomparison studies conducted between TOLNet lidar systems (Leblanc et al, 2018;Wang et al, 2017;Sullivan et al, 2015) showed that O 3 profile concentrations typically agree within ±5%, consistent with system specific propagated errors.…”
Section: The Langley Mobile Ozone Lidar (Lmol)mentioning
confidence: 55%
“…Although the CABOTS ozonesondes were launched too far away from the VMA to allow quantitative comparisons with the lidar, TOPAZ was relocated to the NASA Jet Propulsion Laboratory (JPL) (Leblanc et al, 2018). The results from the SCOOP intercomparison and those presented here complete the inter-validation of the CABOTS lidar, aircraft, and ozonesonde profile measurements.…”
Section: Discussionmentioning
confidence: 90%
“…In this paper, we compare O3 measurements from the NOAA ESRL Tropospheric Optical Profiler for Aerosol and oZone (TOPAZ) lidar with in-situ measurements from nearby regulatory and research surface monitors, and from instruments flown aboard the UC Davis/Scientific Aviation Mooney (Trousdell et al, 2016) and Alpha Jet research aircraft based at NASA's Ames Research Center (Hamill et al, 2016;Yates et al, 2015). These comparisons, together with those from the multi-lidar (including TOPAZ) and ozonesonde Southern California Ozone Observation Project (SCOOP) intercomparison conducted by the NASA-sponsored Tropospheric Ozone Lidar Network (TOLNet) immediately after CABOTS (Leblanc et al, 2018) provide this validation.…”
Section: Introductionmentioning
confidence: 99%
“…Ozone, CO 2 , CH 4 , and other species were also sampled by single‐engine Mooney TLS Bravo and Ovation 2 research aircraft operated by the University of California, Davis (UC Davis) and Scientific Aviation (SciAv) (Trousdell et al, 2019) and by the NASA Alpha Jet Atmospheric eXperiment (AJAX) research aircraft (Yates et al, 2015). Details of the sampling techniques and intercomparisons between the lidar and airborne O 3 measurements are described in Leblanc et al (2018) and Langford et al (2019).…”
Section: The California Baseline Ozone Transport Studymentioning
confidence: 99%